2010
DOI: 10.1080/1350293x.2010.500076
|View full text |Cite
|
Sign up to set email alerts
|

‘Learning to Live Together’: training early childhood educators to promote socio‐emotional competence of toddlers and pre‐school children

Abstract: This paper describes a training program -'Learning to Live Together' -for early childhood educators working with toddlers and preschoolers in daycare or nursery schools. The training aims to provide educators with (a) research-based knowledge on socio-emotional development, and on social 'learning opportunities' offered by daily social and emotional events in the group setting; (b) specific intervention skills that support socio-emotional development; (c) The program further explores and clarifies the overt an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 50 publications
(46 reference statements)
0
18
0
2
Order By: Relevance
“…They have been associated with less aggressiveness and problematic behaviour, positive peer interactions and the development of motivational and learning processes important for academic achievement (Curby et al, 2009;O'Connor & McCartney, 2007). However, research has also suggested that emotional support and sensitive caregiving is a necessary but not sufficient condition for fostering children's socioemotional development and skills (Rosenthal & Gatt, 2010). The presence of other conditions in the childcare environment, such as developmentally appropriate activities that promote social and emotional skills and competencies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been associated with less aggressiveness and problematic behaviour, positive peer interactions and the development of motivational and learning processes important for academic achievement (Curby et al, 2009;O'Connor & McCartney, 2007). However, research has also suggested that emotional support and sensitive caregiving is a necessary but not sufficient condition for fostering children's socioemotional development and skills (Rosenthal & Gatt, 2010). The presence of other conditions in the childcare environment, such as developmentally appropriate activities that promote social and emotional skills and competencies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of other conditions in the childcare environment, such as developmentally appropriate activities that promote social and emotional skills and competencies (e.g. play, positive peer interactions; Bodrova & Leong, 2008;Hollingsworth & Buysse, 2009;Rosenthal & Gatt, 2010), organisational support (classroom organisation and materials, setting up routines, anticipating problems, prevention and redirection of misbehaviour) and strategies to help children learn (experiential learning, scaffolding, encouragement and support to take initiative and voice ideas; Curby et al, 2009) are also necessary for a positive impact on children's socioemotional skills and competence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LtLT consists of both workshops and consultation meetings where teachers focus on learning about young children's experiences in group care, how children show empathy and learn to play together as well as how children resolve conflicts. Further, LtLT gives educators a set of tools to use throughout the teaching day in order to promote children's emotional competence (Rosenthal & Gatt, 2010). The LtLT program has shown considerably good outcomes for teachers as "early childhood teachers reported that the program has changed their understanding and attitude towards their role vis-à-vis social and emotional development of children" (Rosenthal & Gatt, 2010).…”
Section: Importance Of Teachers' Training and Programsmentioning
confidence: 99%
“…Teachers' pedagogical knowledge and sensitivity to children's needs, as well as their comfortable presence with children and their pedagogical contribution to children's development and learning have been recognised in several studies (e.g., Birch & Ladd, 1998;van Manen, 1991), and the opportunities to study such important features of teacher-child interaction through quantitative and variable-centred approaches are limited. Furthermore, as existing studies with a clear emphasis on teachers' practices or pedagogical decisions of teachers are relatively few in number (e.g., Hännikäinen & Rasku-Puttonen, 2010;Rosenthal & Gatt, 2010;Yan, Evans, & Harvey, 2011), it is necessary to add to the limited understanding by exploring individual classrooms and teachers. In addition, as children in preschool classrooms are soon transitioning to primary school, it is worth bearing in mind how daily interaction in the Finnish preschool classrooms is related to the children's preparation to formal schooling.…”
Section: Introductionmentioning
confidence: 99%